COVID-19 vaccine effectiveness among the staff of the Bologna Health Trust, Italy, December 2020-April 2021 - Giansante, Chiara; Stivanello, Elisa; Perlangeli, Vincenza; Ferretti, Filippo; Marzaroli, Paolo; Musti, Muriel Assunta; Pizzi, Lorenzo; Resi, Davide; Saraceni, Simona; Pandolfi, Paolo (Acta Biomedica Atenei Parmensis, 2021)
Background and aim:Randomized controlled trials have shown that mRNA vaccines are highly effective in preventing SARS-CoV2 infection. We conducted a study to assess the real-world effectiveness of mRNA vaccines (Pfizer-BioNTech or Moderna) in preventing all and symptomatic SARS-CoV2 infections and COVID-19 related hospitalizations in the staff of the Bologna Health Trust (HT), ItalyMethods:We followed up retrospectively 9839 staff of the Bologna HT from December 27, 2020 to April 3, 2020 and calculated the effectiveness in partially and fully vaccinated subjects by applying a multivariable Cox proportional hazard model.Results:Vaccine effectiveness in preventing SARS-CoV2 infections is 85.5% (95%CI: 75.9-91.3) in the partially vaccinated and 84.8% (95%CI: 73.2-91.4) in the fully vaccinated. In preventing symptomatic infection effectiveness is 81.7% (95%CI: 62.7-91.0) in the partially and 87.1% (95%CI: 69.3-94.6) in the fully vaccinated. There were no COVID-19-related hospitalizations in the partially or fully vaccinated vs 15 hospitalization in the unvaccinated cohort.Conclusions:Our results confirm the effectiveness of mRNA vaccines in a real-world setting in Northern Italy.